(untitled) (The Research of Medical Science Review, 2025)
Introduction: Type 2 diabetes (T2D) is greatly influenced by lifestyle factors such as obesity, inactivity, and sleep disturbances, all of which contribute to insulin resistance. Micronutrients such as vitamin D play a vital role in regulating sleep by affecting inflammation and brain receptors involved in the sleep-wake cycle. The link between diabetes and sleep is significant, with many patients experiencing poor sleep quality or insomnia, making it crucial to address these issues for effective management of T2D. Methodology: A group of 200 patients with type II diabetes was selected from the Endocrinology Ward at Lady Reading Hospital (LRH) in Peshawar, following their written consent. A self-developed questionnaire was used to collect data on various demographic factors, including age, gender, marital status, education level, income, and family structure. Biochemical records such as blood glucose levels and serum vitamin D were also gathered. Dietary intake patterns were assessed using a semi-quantitative Food Frequency Questionnaire (FFQ) and the 24-hour dietary recall method. Nutrient analysis was performed using Windiet software. Additionally, sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). Data analysis included descriptive statistics and logistic regression models. Major Results: The respondents were primarily male (52%), aged 25–60, and mostly belonging to urban (70%) with a high illiteracy rate (55%) and income below 50,000 PKR. A strong family history of diabetes (80.5%) was observed. Glycemic control was poor (9.59 ± 2.41 in males, 9.51 ± 1.76 in females), with elevated blood pressure (DBP: 81.63 ± 3.73 for males, 83.61 ± 4.91 for females; SBP: 125.00 ± 9.96 for males, 122.33 ± 9.44 for females). Serum vitamin D was low (29.16 ± 5.07 among males, 28.95 ± 4.86 among females). Mean dietary vitamin D for ages 24–49 was 1.67 ± 0.44 (males) and 1.31 ± 0.44 (females), and for ages 50+, it was 3.57 ± 0.51 (males) and 3.51 ± 0.37 (females), all below the RDA. The mean score for sleep quality of male respondents for good sleep and poor sleep was (3.44 ± 0.73) and (9.34 ± 3.52), respectively. The same score for female respondents for good sleep and poor sleep was (3.45 ± 0.60) and (10.60 ± 3.33), respectively. Female respondents had high percentages for sleep latency and daytime dysfunction. Overall, females had poor sleep quality after evaluation of all the parameters. The regression statistics showed a surprisingly positive predictability of hyperglycemia (Hba1c) and Vitamin D deficiency (Serum Vitamin D) for all the sleep parameters and total PSQI scores on the Pittsburgh Sleep Quality Index. Conclusion: The current study concludes that poor glycemic control, widespread hypovitaminosis D, poorer sleep quality among most of females than males with imbalanced dietary patterns and an overall poor sleep quality and vitamin D deficiency which need to be addressed both at the individual and clinical levels.